The Effect of Risk Governance on Financial Performance with Moderation of Top Management Team Diversity - Hadiatmojo, Desian; Anis, Idrianita (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study analyzes the impact of risk governance on financial performance, specifically focusing on profitability, with the moderating role of top management team diversity in terms of age and gender. The research uses a purposive sampling method with a sample of 66 companies from the basic chemical manufacturing sector listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. Data were collected from annual reports, financial statements, and sustainability reports published by these companies, covering information on sustainability disclosure, risk management, corporate governance (CG), and elements of the risk governance framework (RGOV), which include governance at the board of directors (BOD) level, board of commissioners (BOC) level, and risk management processes. indicate that overall risk governance has a positive influence on profitability, although not statistically significant. Governance at the board of directors level has a significant positive effect on profitability, while governance at the management level and risk processes show no significant impact. Age diversity was found to have a significant positive influence on profitability, whereas gender diversity showed no significant effect. Furthermore, age and gender diversity did not moderate the relationship between risk governance and profitability. These findings are expected to provide insights into how management team diversity can improve the effectiveness of risk governance and the company's profitability